Analisis Variance Anggaran Dan Realisasi Belanja Perjalanan Dinas Pada Dinas Kearsipan Provinsi Sumatera Selatan - Emilia Gustini; Viara, Viara Meiza (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
Official travel expenses represent a key component of the operational budget in government institutions, requiring efficient and accountable management. This study aims to analyze, identify contributing factors, and evaluate the effectiveness of budget management and the realization of official travel expenditures at the South Sumatra Provincial Archives Office. A descriptive quantitative method was employed, using variance analysis techniques to compare the allocated budget with actual spending. The data used were secondary data sourced from the 2022 budget report. The analysis results indicate that the management of official travel budgets in 2022 was effective and efficient, with a realization rate of 96.53% of the total allocated budget and a positive variance of 3.47%. This reflects budget efficiency without compromising the quality of activity implementation.